The omega 3 index: a study on the Portuguese population - Cardoso, Carlos; Gomes, Romina; Francisco, João; Sapatinha, Maria; Afonso, Cláudia; Bandarra, Narcisa M. (Intelektual Pustaka Media Utama, 2025)
The omega-3 index (O3I) is used as a biomarker for cardiovascular disease risk. The factors affecting O3I are not fully understood. A study was conducted in a representative sample of the Portuguese population (1,126 individuals) involving blood sampling for the determination of O3I and answering a questionnaire. Participants were asked to indicate their consumption frequencies and other relevant data. The average O3I of the population was 4.82±2.30%. There was a clear increasing trend of the O3I with higher amounts of consumed seafood, achieving an O3I of 6% with three or more weekly meals. Age was a major determinant, presenting 50-79 year old males higher O3I values than 18-49. Physical activity led to higher O3I, 5.05±2.39% vs 4.64±2.21%. Smoking caused a lower O3I, 4.38±1.97% vs 4.89±2.34%. Physical activity had a larger effect upon O3I in consumers with high seafood consumption. In elderly (>70 year old), there was an inverse relation between O3I levels and high blood pressure. This study’s findings point to the importance of changing dietary habits in the direction of increasing seafood consumption and combining these nutritional changes with a healthier lifestyle (with more physical activity and no smoking) for a higher O3I and a lower cardiovascular disease incidence.